Peningkatan Hasil Belajar Matematika melalui Media Realia pada Siswa Kelas 2 SD - Annisa Herlida Sari (Universitas Trunojoyo Madura, 2020)
The aim of this research is to improve the results of learning math students second grade through the application of media realia. The research was implemented on SDN 1 Kalianda, South Lampung. This study used class action research conducted through two cycles, a cycle of comprising planning, action, observation and reflection. The subject of research is a whole number of second grade student SDN 1 Kalianda having the mathematical value helpdown KKM totaled 12 student. Analysis of the percentage data used in this study was based on an agreement with a researcher and collaborator is using percentage increase reched 71% atthe end of the cycle. Analysis of data obtained from the result of percentage increase at the end of the cycle reached 84,33%. The end result of a whole analysis percentage data is an inrease more than 71%. Based on an increase in the percentage of this research, all student have reached percentage inrease reahed 71%, the can be expressed that hypotesis accepted. It could be concluded that the use of the media realia can enchange the results of learning math student second grade of elementary school student.